FIFTH GRADE STUDENTS’ SCIENCE LITERACY PROFILE AS A BASIS FOR DEVELOPING EDUCATIONAL GAMES - Dewi Astuti; wuri wuryandani; Supartinah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Scientific literacy is a fundamental skill that must be developed from elementary school level so that students are able to understand and solve problems based on scientific evidence. This study aims to describe the profile of scientific literacy, identify factors causing low achievement, and formulate recommendations. Using a qualitative case study approach at Kalibawang Public Elementary School, data were collected through questionnaires, observations, and interviews with 30 fifth-grade students and one teacher selected by purposive sampling, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The results show that the profile of students' scientific literacy is in the sufficient category (average 3.16) with gaps between aspects: scientific responsibility competency is the highest (3.29), while science career information (2.85) and environmental responsibility (2.86) are the lowest. Low scientific literacy is caused by three interlocking factors: teachers' limitations in developing textbook-based assessment instruments, the lack of interactive media, and the scarcity of project-based learning due to the dominance of the transmissive pattern. The implication is that teacher training is needed to develop contextual digital instruments and media, allocate time for integrated STEM projects, school policies that support innovative models, and the development of mission-based educational games to improve scientific literacy sustainably.